PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN ISPRING SUITE PADA MATA PELAJARAN INFORMATIKA MATERI PERANGKAT KERAS KOMPUTER - Fahmi Romisa (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
Technology-based learning media has become an important part of modern education. In the context of teaching informatics subjects, the use of android-based learning media can increase the effectiveness of learning. This study aims to develop learning media based on Android using iSpring Suite in informatics subjects, with a focus on computer hardware material. This study uses a multimedia development method which consists of five stages: needs analysis, design, development, evaluation, and implementation. The results showed that the android-based learning media using the iSpring Suite in informatics subjects received positive responses from media experts who were involved in the development process. In conclusion, the development of Android-based learning media using the iSpring Suite in informatics subjects, especially in computer hardware material, can be used as a learning tool for students..